The Role of B7 Family Molecules in Maternal–Fetal Immunity - Zhao, Yongbo; Zheng, Qingliang; Jin, Liping (Frontiers in Immunology, 2020)
Pregnancy is a complex but well-arranged process, and a healthy fetus requires immune privilege and surveillance in the presence of paternally derived antigens. Maternal and fetal cells interact at the maternal-fetal interface. The upregulation and downregulation of maternal immunity executed by the leukocyte population predominantly depend on the activity of decidual natural killer cells and trophoblasts and are further modulated by a series of duplex signals. The B7 family, which consists of B7-1, B7-2, B7-H1, B7-DC, B7-H2, B7-H3, B7-H4, B7-H5, BTNL2, B7-H6 and B7-H7, is one of the most characterized and widely distributed signaling molecule superfamilies and conduct both stimulatory and inhibitory signals through separate interactions. In particular, the roles of B7-1, B7-2, B7-H1 and their corresponding receptors in the progression of normal pregnancy and some pregnancy complicationshave been extensively studied. Together with the TCR-MHC complex, B7 and its receptors play a critical role in cell proliferation and cytokine secretion. Depending on this ligand-receptor crosstalk, the balance between the tolerance and rejection of the fetus is perfectly maintained. This review aims to provide an overview of the current knowledge of the B7 family and its functions in regulating maternal-fetal immunity through individual interactions.